RETRACTED: Delineation of potential managed aquifer recharge sites of Kuchlak sub-basin, Balochistan, using remote sensing and GIS - Sardar, Hassan; Akhter, Gulraiz; Ge, Yonggang; Haider, Syed Ammar (Frontiers in Environmental Science, 2022)
In the Kuchlak Sub-Basin (Pakistan), groundwater is severely over-exploited, resulting in growing stress on groundwater resources. The water table level has declined rapidly due to intensive pumping. The artificial recharge methods and good management strategy are vital for the sustainable production of groundwater resources. Managed aquifer recharge is an artificial way of recharging the subsurface aquifers using surplus surface water, treated wastewater, and stormwater. It is a potential strategy for increasing freshwater supply and adapting to climate change. The present study proposed a method to delineate potential zones for MAR suitability in the Kuchlak sub-basin. INOWAS, a web-based tool is utilized for narrowing down the available MAR techniques based on the hydrogeologic parameter of the study area and the study’s objective. A geographic information system (GIS) coupled with the multi-criteria decision analysis (MCDA), commonly known as GIS-MCDA, is used to develop the MAR suitability map. Six criterion maps, including geology, land use, slope, drainage density, soil, and precipitation, were created in ArcGIS for suitability mapping. The criterion maps are ranked and weighted based on their relative contribution to the groundwater recharge and review of published literature using the Multi Influence Factor (MIF) method. The final suitability map was developed by overlaying all the criterion maps using a weighted linear combination (WLC) technique. The MAR suitability map was divided into five zones, i.e., very high, high, moderate, very low, and low. The unsuitable zones reflect the urban and slope constraint that reduces the surface infiltration. The suitability map reveals that 10% of the Kuchlak sub-basin exists in a very high suitability zone, 60% in moderate-high, and 30% in a very low-low suitability zone, while 10% of the study area was unsuitable due to the urban and slope constraint. The MAR suitability map developed in this study can serve as a base for conducting a focused analysis on MAR implementation. Furthermore, the technique and results of this study may aid in mapping MAR suitability in any arid or semi-arid region.